2010
DOI: 10.1016/j.brat.2010.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Habitual starvation and provocative behaviors: Two potential routes to extreme suicidal behavior in anorexia nervosa

Abstract: Anorexia nervosa (AN) is perhaps the most lethal mental disorder, in part due to starvation-related health problems, but especially because of high suicide rates. One potential reason for high suicide rates in AN may be that those affected face pain and provocation on many fronts, which may in turn reduce their fear of pain and thereby increase risk for death by suicide. The purpose of the following studies was to explore whether repetitive exposure to painful and destructive behaviors such as vomiting, laxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 62 publications
1
73
1
9
Order By: Relevance
“…Direct tests supported the link between self-harm behaviors, acquired capability, and eventually with suicide attempts (Bender, Gordon, Bresin et al, 2011;Joiner, Van Orden, Witte et al, 2009;Selby, Smith, Bulik et al, 2010;Smith, Ribeiro, Mikolajewski et al, 2012;Van Orden, Witte, Cukrowicz et al, 2010;. However, findings regarding increased pain tolerance by non-suicidal self-injury showed inconsistent results (Franklin, Hessel, & Prinstein, 2011;Hooley, Ho, Slater et al, 2010;Nock, Joiner, Gordon et al, 2006).…”
Section: Interpersonal Theory Of Suicide (Ipts)mentioning
confidence: 96%
“…Direct tests supported the link between self-harm behaviors, acquired capability, and eventually with suicide attempts (Bender, Gordon, Bresin et al, 2011;Joiner, Van Orden, Witte et al, 2009;Selby, Smith, Bulik et al, 2010;Smith, Ribeiro, Mikolajewski et al, 2012;Van Orden, Witte, Cukrowicz et al, 2010;. However, findings regarding increased pain tolerance by non-suicidal self-injury showed inconsistent results (Franklin, Hessel, & Prinstein, 2011;Hooley, Ho, Slater et al, 2010;Nock, Joiner, Gordon et al, 2006).…”
Section: Interpersonal Theory Of Suicide (Ipts)mentioning
confidence: 96%
“…Although these behaviors are often painful (Claes, Vandereycken, & Vertommen, 2006;Selby et al, 2010) and carry a risk of negative emotional and social consequences (Leibenluft, Gardner & Cowdry, 1987), they often serve to reduce unwanted emotions and other internal experiences (Haynos & Fruzzetti, 2011;Heatherton & Baumeister, 1991;Klonsky, 2007;Smyth et al, 2007). Current theories posit that the immediate reduction in negative affect provides powerful reinforcement such that these behaviors are repeated despite negative consequences that can accumulate over the long term (Chapman, Gratz, & Brown, 2006;Fairburn, Cooper, & Shafran, 2003;Haynos & Fruzzetti, 2011;Heatherton & Baumeister, 1991).…”
mentioning
confidence: 99%
“…For instance, Stein et al (2003) found that women with bulimia nervosa (BN) who had been recovered for a year still had elevated pain thresholds compared to healthy controls. Further, Selby et al (2010) found two distinct routes to extreme suicidal behavior among individuals with AN: for the AN-BP subtype, behaviors such as vomiting, laxative use, drug abuse, and non-suicidal self-injury were associated with suicide attempts, whereas for the AN-R subtype, unwavering restriction was related to past attempts.…”
Section: Disordered Eating and Acquired Capability For Suicidementioning
confidence: 99%
“…Using the IPTS as a framework, Selby et al (2010) and Smith et al (2013Smith et al ( , 2014 speculated that behaviors related to eating disorders, like extreme dietary restriction, binging, and purging, constitute instances of pain and provocation. Specifically, these researchers hypothesized that because individuals with eating disorders must engage in painful behaviors to keep their weight low, they may habituate to pain, which would increase their pain tolerance and ACS and thereby increase their risk for death by suicide.…”
Section: Disordered Eating and Acquired Capability For Suicidementioning
confidence: 99%